Characterization of forms of violence perpetrated against women during the quarantine period for COVID-19 - Barreto , Ana Cláudia Mateus; Santos , Rosângela da Silva; Louro , Thiago Quinellato; Teixeira , Selma Villas Boas; Ribeiro, Yonara Cristiane; Dantas, Claudia de Carvalho; Oliveira, Luíza Pereira Maia de; Lopes, Mayara Martins (Seven Editora, 2023)
Introduction: Social isolation during the COVID-19 pandemic was considered effective in protecting the health of the population, however, it contributed to the emergence of barriers that prevented women from fleeing different situations of violence and seeking help.  Objective: to characterize the forms of violence perpetrated against women during the quarantine period for Covid-19.  Method: quantitative, cross-sectional, descriptive research. Approved by the Ethics and Research Committee of Universidade Federal Fluminense (CAAE: 45939421.1.0000.8160). Data collected by questionnaire from May and August 2022. Its participants were 278 women from social media. Included were those who had experienced some situation regarding domestic violence in their relationship with their current partner or with a partner from a previous relationship, and had access to the digital form and excluded women who had not experienced situations of domestic violence both in their relationship with their partner (a) current and with a partner (a) from a previous relationship,  inability to complete the digital form. Data computed, stored and analyzed in software through tables, graphs and charts with simple and percentage frequencies. Results: It was found that 35.6% of the study participants had already been assaulted by their current partner, or from a previous relationship. Regarding the current partner, or a previous relationship that was already violent before the quarantine period, it was found that 12.2% of the study participants stated that their current partner, or a partner previous relationship was already violent before the quarantine period. Regarding the current partner, or a previous relationship having become more violent during the quarantine period, it was found that 10.8% of the study participants stated that their current partner, or from a previous relationship became more violent during the quarantine period. It was found that 33.5% of the study participants had already suffered physical violence committed by their current partner, or from a previous relationship. It was found that 14% did not suffer physical violence before the quarantine period, and started to suffer, 2.9% suffered physical violence before the quarantine period, and continued to suffer during the quarantine period, 3.2% suffered physical violence before the quarantine period, and worsened during the quarantine period, 9.7% of the study participants had already suffered physical violence before the quarantine period. It was found that 44.2% of the study participants had already suffered psychological violence committed by your current partner, or from a previous relationship. It was found that 7.2% did not suffer psychological violence before the quarantine period, and began to suffer, 16.2% suffered psychological violence before the quarantine period, and continued to suffer during the quarantine period, 5% suffered psychological violence before the quarantine period, and it worsened during the quarantine period, and 11.2% of the study participants had already suffered psychological violence before the quarantine period,  and now do not suffer. It was found that 21.2% of the study participants study had already suffered sexual violence. It was found that 1.8% did not suffer sexual violence before the quarantine period, and started to suffer, 1.8% suffered sexual violence, and continued to suffer, 1.8% suffered, and it got worse during the quarantine period, 7 .6% of women already suffered sexual violence before the quarantine period, and now they do not suffer. Conclusion: Domestic violence affects women regardless of race, social class and education. However, those with low education, single/separated/divorced/widow and lower family income suffered more violence. The elaboration of public policies to combat violence is reinforced considering race/class, since the absence of this view favors society's denial of inequalities that are not restricted to gender issues. The need for professional training and an empathetic look in the care of these women is highlighted. DOI:https://doi.org/10.56238/emerrelcovid19-033